Hemingway the man. The myth. The writer revealed. - Ward, Geoffrey C. 1940- (The Hemingway Film Project, LLC, 2021)
"Examine the visionary work and turbulent life of one of the greatest and most influential American writers: Ernest Hemingway. Intimate and insightful, the series weaves together Hemingway's biography with excerpts from his work. The film penetrates the myth of Hemingway to reveal a deeply troubled and ultimately tragic figure." (Rückseite der DVD-Hülle)
Ursprünglich als dreiteilige Dokumentation vom Fernsehsender PBS ausgestrahlt. (2021)
Episoden: 1. "A writer (1899-1929)", 2. "The avatar (1929-1944)", 3. "The blank page (1944-1961)"
Ton: Englisch: 5.1 Surround, Spanisch: 2.0 Stereo
Titelzusatz dem Cover der DVD-Hülle entnommen
Widescreen (16x9)
Keywords: Hemingway, Ernest -- 1899-1961; Hemingway, Ernest / 1899-1961; Authors, American / 20th century / Biography; Autores estadounidenses / Siglo XX / Biografía; Authors, American; 1900-1999; Television mini-series; Nonfiction television programs; Documentary television programs; Biographical television programs; Biographies; Video recordings for the hearing impaired; Film; DVD-Video